The effect of sulphur in fuel on the performance of automotive catalysts - Siemelink, Johannes Jacobus (Energy Research Centre, 2016)
Catalysts have been used on cars since 1974 to reduce tailpipe emission levels of carbon monoxide, hydrocarbons and oxides of nitrogen. Initially, oxidation catalysts were used that operated under very lean air/fuel conditions and gave rise to increased sulphate particulate emissions. These sulphate emissions could fortunately be reduced by better air/fuel control. However, the introduction of more active catalyst compositions, in particular the use of cerium oxide components on the wash coat, led to bad odour complaints from motorists. In the report it is shown that under fuel-lean conditions, sulphur, originating from the fuel, is stored as aluminium and cerium sulphates onto the washcoat. Upon a rapid change to fuel-rich engine operation the stored sulphates are released as hydrogen sulphide and is the cause for the smell observed. The sulphur storage/release process results in hydrogen sulphide emissions many times higher than is possible from steady-state conversion from the fuel sulphur level. By using a catalyst/engine combination on a testbed the experiments have shown that the hydrogen sulphide release is a kinetically limited reaction and, apart from the air/fuel control, depends mainly on the catalyst temperature.